2007
DOI: 10.1002/dev.20181
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neonatal novelty exposure on sexual behavior, fear, and stress‐response in adult rats

Abstract: Environmental stimuli in early life may result in permanent behavioral and physiological changes. Present study evaluated the effects of exposing pups to a novel environment on behaviors (open-field test and sexual behavior) and prolactin stress-responses in adult male rats. Half of a litter was daily removed outside (OUT) from the nest and stimulated by handling for 3 min, while the other half remained inside (IN) the nest and was also handled for the same period during the first 10 days postpartum. Maternal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 35 publications
1
23
1
5
Order By: Relevance
“…While higher quantity of maternal care has been shown to be associated with increased GR expression (Liu et al, 1997;Francis et al, 1999), here it is unlikely that the memory enhancement induced by novelty exposure is due solely to a greater amount of maternal care, because dams, whether high or low caregivers, did not show preferential care toward the novelty-exposed pups (Tang et al, 2006;Benetti et al, 2007). It is possible, and remains to be determined, whether the previously reported association between quantity of maternal care and offspring GR expression may be due to differences in dams' circulating corticosterone level, as manipulation of dams' circulating corticosterone is known to result in changes in the offspring's HPA function and spatial memory, likely through the mother's milk (Catalani et al, 1993(Catalani et al, , 2000(Catalani et al, , 2010.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…While higher quantity of maternal care has been shown to be associated with increased GR expression (Liu et al, 1997;Francis et al, 1999), here it is unlikely that the memory enhancement induced by novelty exposure is due solely to a greater amount of maternal care, because dams, whether high or low caregivers, did not show preferential care toward the novelty-exposed pups (Tang et al, 2006;Benetti et al, 2007). It is possible, and remains to be determined, whether the previously reported association between quantity of maternal care and offspring GR expression may be due to differences in dams' circulating corticosterone level, as manipulation of dams' circulating corticosterone is known to result in changes in the offspring's HPA function and spatial memory, likely through the mother's milk (Catalani et al, 1993(Catalani et al, , 2000(Catalani et al, , 2010.…”
Section: Discussionmentioning
confidence: 67%
“…However, there have been recent findings suggesting that maternal care alone is neither sufficient nor necessary for the production of stimulation-induced effects (Denenberg, 1999;Pryce and Feldon, 2003;Macrì and Würbel, 2006;Parker et al, 2006;Tang et al, 2006) and that other environmental variables that affect the offspring or the mother's HPA function can also powerfully influence offspring development (Moriceau and Sullivan, 2006;Parker et al, 2006;Tang et al, 2006;Benetti et al, 2007;Akers et al, 2008;Raineki et al, 2010;Catalani et al, 2011). Most importantly, in studies using the postnatal/neonatal handling procedure, maternal care is intrinsically confounded with the maternal stress hormone and with offspring's stress experience (see Materials and Methods) (Russell, 1971;Daly, 1973;Tang, 2001), and these confounding factors cannot be ruled out by using a cross-fostering experimental design as by Liu et al (1997) and Francis et al (1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early and abrupt separation also enhances manifestations of anxiety and depression-like behaviors (Fabricius et al, 2008;Lambás-Señas et al, 2009) and impairs spatial learning and memory (Aisa et al, 2007;Tata et al, 2015) during adulthood. In contrast, repeated, short maternal separation increased resilience to stressful events later in life (Parker et al, 2006;Benetti et al, 2007) and reduced fearfulness (Macrì and Würbel, 2006). The positive effects of such separations may have resulted from increased attention from the mother when the pups were returned.…”
Section: Management Of Weaningmentioning
confidence: 99%
“…The results obtained in the open field test showed that the treatment of rat dams with oregano essential oil did not affect the emotional state of the offspring. Studies have shown that stressful stimuli during the period of sexual differentiation of the central nervous system, prenatal and soon after birth induce stable changes manifested by decreased sexual behavior in male and female rats (BENNETI et al, 2007).…”
Section: Hollenbach Et Almentioning
confidence: 99%